Persepsi E-learning Dengan Kepuasan Belajar Mahasiswa Pada Masa Pandemi - Israwati Hamsar; Niswa Nurpratiwi; Maulidyah Juniarti Yunus; Nur Azizah Ayu Safanah; Sri Erfiana Nur; M Ismul Azzam (Jurnal Pendidikan Terapan, 2023)
The purpose of this study was conducted to determine students' perceptions of e-learning towards learning satisfaction during a pandemic. The research design was carried out with quantitative descriptive research with an online questionnaire type data collection model (google form) for active students during the pandemic and the data analysis technique used was descriptive analysis. The results showed that 67% of students knew and were able to use online learning, 51% of students supported the implementation of online learning, and 37% of students expressed satisfaction with online learning. The results of the data in general, show an analysis that the perception of e-learning with student learning satisfaction during the pandemic states that it is useful, and can increase motivation, facilitate and take learning materials, and can help readiness in online learning. Based on the analysis conducted by researchers, a conclusion can be drawn that students have a high commitment in terms of distance or online learning during the pandemic. Assessment of the perception of student satisfaction with online learning services by providing a large role in its implementation can be done with google classroom services and zoom meetings as learning platforms.